Modulation of entorhinal cortex–hippocampus connectivity and recognition memory following electroacupuncture on 3×Tg-AD model: Evidence from multimodal MRI and electrophysiological recordings - Lin, Bingbing; Zhang, Lanlan; Yin, Xiaolong; Chen, Xiaocheng; Ruan, Chendong; Wu, Tiecheng; Liu, Zhizhen; Huang, Jia (Frontiers in Neuroscience, 2022)
Memory loss and aberrant neuronal network activity are part of the earliest hallmarks of Alzheimer’s disease (AD). Electroacupuncture (EA) has been recognized as a cognitive stimulation for its effects on memory disorder, but whether different brain regions or neural circuits contribute to memory recovery in AD remain unknown. Here, we found that memory deficit was ameliorated in 3×Tg-AD mice with EA treatment, as shown by increased number of exploring and time spent in novel object. In addition, reduced locomotor activity was observed in 3×Tg-AD mice, but no significant alteration was seen in the EA-treated mice. Base on the functional magnetic resonance imaging, the regional spontaneous activity alteration of 3×Tg-AD was mainly concentrated in accumbens nucleus, auditory cortex, caudate putamen, entorhinal cortex, hippocampus, insular cortex, subiculum, temporal cortex, visual cortex and so on. While EA-treatment prevented the chaos of brain activity in parts of the above regions, such as auditory cortex, entorhinal cortex, hippocampus, subiculum, temporal cortex. And then we used the whole-cell voltage-clamp recording to reveal the neurotransmission in the hippocampus, and found that EA-treatment reversed the synaptic spontaneous release. Since the hippocampus receives most of the projections of entorhinal cortex, and the hippocampus- entorhinal cortex circuit is one of the neural circuits related to memory impairment. We further applied diffusion tensor image (DTI) tracking and function connectivity and found that hypo-connected between hippocampus and entorhinal cortex with EA-treatment. These data indicate that the hippocampus- entorhinal cortex connectivity is responsible for the recognition memory deficit in the AD mice with EA-treatment, and provide novel insight into potential therapies for memory loss in AD.